Perception of Cityscape of the Central Part of Kaunas and Sociocultural Aspects Determining It - Vaitkutė Eidimtienė, Vaida; Kamičaitytė, Jūratė (Landscape Architecture and Art, 2021)
This article deals with peculiarities of Kaunas centre cityscape perception and the determining socio-cultural factors. Important elements creating unique view of a location and identity are related to the period’s history, culture, political situation, features of the location natural basis, as well as individual’s-observer‘s education, personal qualities, aesthetic and cultural sophistication. The territory of Kaunas city centre was selected for the case study. It is characterized by unique natural, historic, cultural conditions and high information-emotional potential. During the research prioritary ranking concerning significance of cityscape elements groups and experienced psycho-emotional senses was conducted. Furthermore, the correlations between the distance of object observation, heights of observation points as well as movement mode selection and personal factors such as gender, age, occupation, and education based on statistical dependencies were identified. The obtained results explain the principles of Kaunas centre cityscapes perception.